Minimally Invasive Left Ventricular Assist Device: Implantation Implementation Early in a Surgical Career. Issue 3 (May 2018) - Voorhees, Hannah J.; Sorensen, Erik N.; Pasrija, Chetan; Boulos, Francesca M.; Pham, Si M.; Griffith, Bartley P.; Kon, Zachary N.
Objective: Several centers have presented minimally invasive surgical approaches to centrifugal left ventricular assist device implantation. Although minimally invasive implantation has been successfully performed by experienced surgeons, at large implanting centers, it is unknown whether these techniques are widely adoptable. We evaluated the experience of a surgeon early in his career with conventional and minimally invasive approaches to device implantation. Methods: All consecutive left ventricular assist device implantations by a single surgeon in the first year of practice (2015–2016) were retrospectively reviewed. Patients were stratified by standard approach, conventional full sternotomy versus a minimally invasive approach, left anterior thoracotomy and upper hemisternotomy. Demographics, perioperative variables, and short-term outcomes were compared using Wilcoxon rank-sum test. Results: Thirteen patients were identified: six performed via the standard approach and seven performed via the minimally invasive approach. Preoperative demographics were comparable in both groups. However, there was significantly more preoperative right ventricle dysfunction in the minimally invasive group ( P = 0.01). Although operative time was significantly longer in the minimally invasive cohort, there was a trend toward decreased cardiopulmonary bypass time. Six-month survival in both groups was 100%. Conclusions: Compared with conventional sternotomy, minimally invasive ventricular assist device implantation, performed by a surgeon in his first year of practice, had similar perioperative outcomes and excellent survival. Based on these data, minimally invasive implantation may be a feasible strategy for device implantation even early in a surgeon's career.